Reimagining Social Work Placements in the Covid-19 Pandemic. (30th June 2022) - O'Keeffe, Patrick; Haralambous, Betty; Egan, Ronnie; Heales, Emily; Baskarathas, Sobika; Thompson, Scott; Jerono, Caroline
Abstract: The Covid-19 pandemic has fundamentally changed how social work education is provided, and these changes are particularly pronounced in field education. Globally, the introduction of restrictions on mobility and social interaction have contributed to the cancellation, postponement and early termination of social work field placements. Accrediting bodies, social work field education departments and industry partner agencies have needed to rapidly adapt how placements are conceptualised and provided. This article examines the experiences of agencies who have continued to provide student placements throughout the pandemic. Interviews were conducted with placement supervisors employed at twelve human services agencies partnering with a university social work department in Melbourne, Australia. Whilst experiencing challenges, agencies outlined how they adapted to the environment to enable meaningful student placement experiences. This article contributes to an ongoing discussion around the trajectory of social work field education and the significance of agency-based placements in this evolution. Abstract : This article examines the experiences of industry partner agencies who have continued to provide student placements throughout the pandemic. Interviews were conducted with placement supervisors employed at twelve human services agencies partnering with a university social work department in Melbourne, Australia. Whilst experiencing challenges, agencies outlined how they adapted to the environment to enable meaningful student placement experiences. This article contributes to an ongoing discussion around the trajectory of social work field education, and the significance of agency-based placements in this evolution. Rather than separating field education from industry, we suggest that as educators we can learn from industry about how to adapt field education to the changed context that our graduates will be working in.